Business Basics / A Study Guide for Degree Students (Bpp Publishing, 1997)
The book gives substantial coverage of core topics which highlights key definitions, and builds a solid foundation for further study and for the use of business knowledge and skills in practice. Preface, The Nature and Scope of Economics, Price Theory - Supply and Demand, Elasticity of Demand and Supply, Market Failure: Externalities and Intervention, Theory of the Firm: Production and Costs, Factor Markets and Factor Rewards, Market Structures: From Perfect Competition to Monopoly, Monopolistic Competition and Oligopoly, Money and Banking, The Central Bank and the Financial Markets, National Income Analysis, National Income and Unemployment, Unemployment and Inflation, The Demand for and Supply of Money, Fiscal Policy, International Trade, The Balance of Payments and Exchange Rates, Glossary, Index.